Perfluoropolyether modified polysilazane, surface treatment agent, cured film and article
By using only the perfluoropolyol modified polysilicon of silicone phenol units, and through partial fluorination and adsorption treatment technology, the problem of insufficient durability of polysilicon phenol under UV radiation in the prior art is solved, and high UV resistance and water repelent oil repelent properties are achieved.
Patent Information
- Application Number
- JP2019226428
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2019-12-16
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2039-12-16
AI Technical Summary
In the prior art, despite the presence of improved surface treatment agents of water repelent oil repelent properties and surface slip properties, their UV resistance is still insufficient, especially due to insufficient durability of perfluoropolyol modified polysilicon with --C-O-C-bond under UV radiation, which makes it difficult to meet applications requiring high UV resistance.
Using polysiliconol modified with perfluoropolyol composed of silicon phenol units, the end end of the fluoropolyol was partially fluorinated to retain only one end of the functional polysilicon phenol unit, and the functional polysilicon phenol units at one end were extracted through adsorption treatment, and polysilicon phenol with high UV resistance was successfully synthesized.
The high UV resistance of polysilicon is achieved, while the water repelent oil repelent properties and surface slip properties are reduced, and the water repelency reduction after UV radiation is ensured, ensuring performance stability under long-term UV radiation.
Smart Images

Figure 0007662303000001 
Figure 0007662303000002 
Figure 0007662303000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a novel perfluoropolyether modified polysilazane. hmm, The present invention relates to a surface treatment agent containing the polysilazane, a cured coating, and an article having the cured coating. [Background technology]
[0002] Polysilazanes are compounds with Si-N-Si bonds and are highly reactive. Taking advantage of this reactivity, they are used in surface treatment agents, etc. However, because they are highly reactive, they are difficult to handle and may gel or polymerize during synthesis.
[0003] Perfluoropolyether-modified polysilazanes are generally produced by converting perfluoropolyethers having functionality at only one end into silazane. This is because using perfluoropolyethers having functionality at both ends often results in gelation during the reaction. [(CF 2 O) p (CF 2 CF 2 O) q Perfluoropolyethers having this main chain structure are believed to have excellent dirt-removal properties, but only those functionalized at both ends are commercially available.
[0004] In JP 2010-43251 A (Patent Document 1), a compound represented by the following formula (A) is described. F(C x F2 x O) m C y F 2y -Q-Si(NH) 1.5 (A) (In the formula, Q is a divalent organic group, m is an integer of 1 or more, and x and y are each an integer of 1 to 3.) It is disclosed that the perfluoropolyether-modified polysilazane shown in the above is excellent in water and oil repellency, alkali resistance, etc.
[0005] However, even the perfluoropolyether-modified polysilazane disclosed in the examples of the above publication still does not provide satisfactory performance in terms of surface slipperiness and ease of wiping off dirt.
[0006] In JP 2014-105235 A (Patent Document 2), a compound represented by the following formula (B) is described. F(CF 2 O) p (CF 2 CF 2 O) q (CF 2 CF 2 CF 2 O) r (CF 2 CF 2 CF 2 CF 2 O) s -C x F 2x -Q-Si(NH) 1.5 (B) (In the formula, Q is a divalent organic group, p and q are integers of 1 or more, r and s are integers of 0 or more, and each repeating unit may be bonded randomly. x is an integer of 1 to 3.) It is disclosed that the perfluoropolyether-modified polysilazane shown in is excellent in surface slipperiness, water and oil repellency, alkali resistance, etc.
[0007] However, even the perfluoropolyether-modified polysilazane disclosed in the examples of the above publication still did not have satisfactory UV resistance. In particular, the -COC- bond contained in the above perfluoropolyether-modified polysilazane has an oxygen atom (heteroatom) between carbon and carbon, so it has poor UV resistance and is unsuitable for applications requiring these properties.
[0008] The industrial sector demands surface treatment agents that are highly reactive and have excellent UV resistance, water and oil repellency, surface slipperiness, and ease of wiping off dirt.
[0009] As a prior art related to the present invention, JP 2015-101624 A (Patent Document 3) provides a perfluoropolyether polymer having an allyl group at the end without a heteroatom, as shown in the following formula (C). CF 3 O-(CF 2 O) p (C 2 F 4 O) q -CF 2 CH 2 CH 2 CH=CH 2 (C) (p:q=47:53, p+q≒45) [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2010-43251 A [Patent Document 2] JP 2014-105235 A [Patent Document 3] JP 2015-101624 A Summary of the Invention [Problem to be solved by the invention]
[0011] The present invention has been made in view of the above circumstances, and provides a novel perfluoropolyether-modified polysilazane useful as a surface treatment agent having high reactivity and excellent UV resistance, water and oil repellency, surface slipperiness, and ease of wiping off dirt. hmm, The object of the present invention is to provide a surface treatment agent containing the polysilazane, a cured coating, and an article having the cured coating. [Means for solving the problem]
[0012] As a result of intensive research conducted by the present inventors in order to achieve the above object, they have found that a perfluoropolyether-modified polysilazane consisting only of a silazane unit represented by the following formula (1) is useful as a surface treatment agent having high reactivity, excellent water and oil repellency, surface slipperiness, ease of wiping off dirt, and excellent UV resistance, and have thus completed the present invention. [ka] (In the formula, Q is an unsubstituted divalent hydrocarbon group having 3 to 12 carbon atoms, p, q, r, and s are integers of 0 or more, p+q+r+s is an integer of 4 to 200, and each repeating unit may be bonded randomly. x is an integer of 1 to 3.)
[0013] In producing the above-mentioned perfluoropolyether-modified polysilazane, the inventors partially fluorinated the ends of perfluoropolyether having both terminal carboxylic acids to obtain a mixture of one-terminated polymer and non-functional polymer, and then extracted only one-terminated polymer by adsorption treatment. Using this one-terminated raw material, they succeeded in synthesizing one-terminated functional perfluoropolyether-modified polysilazane.
[0014] In addition, in the above-mentioned Patent Document 1, [(CF 2 O) p (CF 2 CF 2 O) q In addition, the above-mentioned Patent Document 1 mainly discloses [ka] The present invention shows a silazane having a branched repeating unit represented by the formula: 2 Units of O and CF 2 CF 2 O units or CF 2 CF 2 CF 2 In the present invention, CF 2 CF 2 O, C.F.2 CF 2 CF 2 O and CF 2 CF 2 CF 2 CF 2 All O units are linear, and the silazane of the present invention does not contain branched perfluoroether units or perfluoropolyether units.
[0015] Therefore, the present invention provides the following perfluoropolyether modified polysilazane. hmm, The present invention provides a surface treatment agent, a cured coating, and an article. [1] A perfluoropolyether-modified polysilazane consisting only of silazane units represented by the following formula (1). [ka] (In the formula, Q is a group having 3 to 12 carbon atoms. is an alkylene group p, q, r, and s are integers of 0 or more, p+q+r+s is an integer of 4 to 200, and each repeating unit may be bonded randomly. x is an integer of 1 to 3. [2] In the above formula (1), [ka] The perfluoropolyether portion represented by the following formula: [ka] (In the formula, p, q, r, and s are the same as above, and each repeating unit may be bonded randomly.) The perfluoropolyether-modified polysilazane according to [1], which is represented by any one of the following: [3] In the formula (1), Q is a compound having 3 carbon atoms. or 4 The perfluoropolyether-modified polysilazane according to [1] or [2], wherein the alkylene group is [4] Wavelength 300~400nm, irradiance 770W / m 2The perfluoropolyether-modified polysilazane according to any one of [1] to [3] above, which gives a cured product in which the rate of decrease in water repellency after 180 hours of irradiation with UV light is 15% or less compared to before irradiation with UV light. [ 5 〕 A surface treatment agent comprising the perfluoropolyether-modified polysilazane according to any one of [1] to [4]. [ 6 〕 A cured coating film of the perfluoropolyether-modified polysilazane according to any one of [1] to [4]. [ 7 〕 A substrate and a film having a structure formed on the surface of the substrate, 6 and a cured coating of the perfluoropolyether-modified polysilazane according to claim 1. [ 8 〕 The substrate is a touch panel, an anti-reflection film, a cover glass for a display, a reinforced glass, a glass for a transport machine, a hard coat film, a cover film for a display, quartz, an optical member, a sanitary product, a glass tableware or a building material. 7 ] The article described in. Effect of the Invention
[0016] The perfluoropolyether-modified polysilazane of the present invention reduces the surface free energy of the polymer due to the action of the fluorooxyalkylene groups, making it possible to obtain a cured product that is superior in water and oil repellency, releasability, chemical resistance, lubricity, durability, stain resistance, and fingerprint wiping removability. Furthermore, since the polymer terminals do not contain heteroatoms and the linking sites are formed only with carbon-carbon (C-C) bonds, it is possible to obtain a cured product that has excellent UV resistance in addition to the above properties. The surface treatment agent containing the perfluoropolyether-modified polysilazane of the present invention is superior in UV resistance, surface slipperiness, and dirt wiping ability to conventional silazane-based water- and oil-repellent treatment agents, and has a faster reaction rate than conventional hydrolyzable water- and oil-repellent treatment agents. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Hereinafter, an embodiment of the present invention will be described. The perfluoropolyether-modified polysilazane of the present invention is composed only of units represented by the following formula (1). [ka] (In the formula, Q is an unsubstituted divalent hydrocarbon group having 3 to 12 carbon atoms, p, q, r, and s are integers of 0 or more, p+q+r+s is an integer of 4 to 200, and each repeating unit may be bonded randomly. x is an integer of 1 to 3.)
[0018] In formula (1), Q is an unsubstituted divalent hydrocarbon group having 3 to 12 carbon atoms, which does not contain an amide bond, an ether bond, an ester bond, or a structure consisting of a diorganosilylene group. 2 CH 2 CH 2 -, -CH 2 CH 2 CH 2 CH 2 and alkylene groups having 3 to 12, preferably 3 or 4, carbon atoms, such as -.
[0019] p is an integer of 0 or more, preferably an integer of 1 to 80, more preferably an integer of 3 to 30, q is an integer of 0 or more, preferably an integer of 1 to 80, more preferably an integer of 3 to 30, r is an integer of 0 or more, preferably an integer of 0 to 20, more preferably an integer of 0 to 5, s is an integer of 0 or more, preferably an integer of 0 to 20, more preferably an integer of 0 to 5. p+q+r+s is an integer of 4 or more and 200 or less, preferably an integer of 5 or more and 100 or less, more preferably an integer of 8 or more and 10 or less. Each repeating unit may be bonded randomly. In addition, x is an integer of 1 to 3, and particularly 1.
[0020] As the polysilazane, in particular, the polysilazane represented by the following formula [ka] It is preferable that the perfluoropolyether moiety represented by the formula is any one of the following formulae: [ka] (In the formula, p, q, r, and s are the same as above. Each repeating unit may be bonded randomly.)
[0021] Specific examples of the unit represented by formula (1) include those represented by the following formula: The repeating units may be bonded randomly. F(CF 2 O) p' (C 2 F 4 O) q' -CF 2 C 3 H 6 -SiNH 1.5 (wherein p' is 3, q' is 3; p' is 9, q' is 8; p' is 8, q' is 9; p' is 13, q' is 12; or p' is 12, q' is 13.) F(CF 2 O) p' (C 2 F 4 O) q' -CF 2 C 4 H 8 -SiNH 1.5 (wherein p' is 3, q' is 3; p' is 9, q' is 8; p' is 8, q' is 9; p' is 13, q' is 12; or p' is 12, q' is 13.) F(CF 2 O) p' (C 2 F 4 O) q' -CF 2 C 5 H 10 -SiNH 1.5 (wherein p' is 3, q' is 3; p' is 9, q' is 8; p' is 8, q' is 9; p' is 13, q' is 12; or p' is 12, q' is 13.) F(CF 2 O) p' (C 2 F4 O) q' -CF 2 C 6 H 12 -SiNH 1.5 (wherein p' is 3, q' is 3; p' is 9, q' is 8; p' is 8, q' is 9; p' is 13, q' is 12; or p' is 12, q' is 13.) F(CF 2 O) p' (C 2 F 4 O) q' -CF 2 C 7 H 14 -SiNH 1.5 (wherein p' is 3, q' is 3; p' is 9, q' is 8; p' is 8, q' is 9; p' is 13, q' is 12; or p' is 12, q' is 13.) F(CF 2 O) p' (C 2 F 4 O) q' -CF 2 C 8 H 16 -SiNH 1.5 (wherein p' is 3, q' is 3; p' is 9, q' is 8; p' is 8, q' is 9; p' is 13, q' is 12; or p' is 12, q' is 13.) F(CF 2 O) p' (C 2 F 4 O) q' -CF 2 C 9 H 18 -SiNH 1.5 (wherein p' is 3, q' is 3; p' is 9, q' is 8; p' is 8, q' is 9; p' is 13, q' is 12; or p' is 12, q' is 13.) F(CF 2 O) p' (C 2 F 4 O) q' -CF 2 C 10 H 20 -SiNH 1.5 (wherein p' is 3, q' is 3; p' is 9, q' is 8; p' is 8, q' is 9; p' is 13, q' is 12; or p' is 12, q' is 13.) F(CF 2 O) p' (C 2 F 4 O) q' -CF 2 C 11 H 22 -SiNH 1.5 (wherein p' is 3, q' is 3; p' is 9, q' is 8; p' is 8, q' is 9; p' is 13, q' is 12; or p' is 12, q' is 13.) F(CF 2 O) p' (C 2 F 4 O) q' -CF 2 C 12 H 24 -SiNH 1.5 (wherein p' is 3, q' is 3; p' is 9, q' is 8; p' is 8, q' is 9; p' is 13, q' is 12; or p' is 12, q' is 13.) F(C 3 F 6 O) r' -CF 2 CF 2 C 3 H 6 -SiNH 1.5 (In the formula, r' is 6, 7 or 8.) F(C 3 F 6 O) r' -CF 2 CF 2 C 4 H 8 -SiNH 1.5 (In the formula, r' is 6, 7 or 8.) F(C 3 F 6 O) r' -CF 2 CF 2 CF 2 C 3 H 6 -SiNH1.5 (In the formula, r' is 6, 7 or 8.) F(C 3 F 6 O) r' -CF 2 CF 2 CF 2 C 4 H 8 -SiNH 1.5 (In the formula, r' is 6, 7 or 8.) F(CF 2 O) p' (C 2 F 4 O) q' (C 4 F 8 O) s' -CF 2 C 4 H 8 -SiNH 1.5 (In the formula, p' is 1, q' is 4, and s' is 3.) F(CF 2 O) p' (C 2 F 4 O) q' (C 4 F 8 O) s' -CF 2 C 6 H 12 -SiNH 1.5 (In the formula, p' is 1, q' is 4, and s' is 3.) F(CF 2 O) p' (C 2 F 4 O) q' (C 4 F 8 O) s' -CF 2 CF 2 CF 2 C 4 H 8 -SiNH 1.5 (In the formula, p' is 1, q' is 4, and s' is 3.) F(CF 2 O) p' (C2 F 4 O) q' (C 4 F 8 O) s' -CF 2 CF 2 CF 2 C 6 H 12 -SiNH 1.5 (In the formula, p' is 1, q' is 4, and s' is 3.) The molecular structure of the perfluoropolyether-modified polysilazane is not limited to these examples.
[0022] The perfluoropolyether-modified polysilazane of the present invention has a wavelength of 300 to 400 nm and an irradiance of 770 W / m 2 It is desirable to provide a cured product in which the rate of decrease in water repellency after 180 hours of irradiation with UV light is preferably 15% or less (0 to 15%), more preferably 12% or less (0 to 12%), and particularly preferably 10% or less (0 to 10%) compared to before irradiation with UV light. The water repellency referred to here is indicated by the contact angle of the cured film (cured product) with water, and is measured using a contact angle meter (e.g., DropMaster (manufactured by Kyowa Interface Science Co., Ltd.)) for a cured film formed on glass using the perfluoropolyether-modified polysilazane of the present invention. The reduction rate of water repellency = (water repellency (contact angle) of the cured film before UV light irradiation - water repellency (contact angle) of the cured film after UV light irradiation) / (water repellency (contact angle) of the cured film before UV light irradiation) x 100 (%).
[0023] [Manufacturing method] The method for producing the perfluoropolyether-modified polysilazane of the present invention includes, for example, a production method including the following steps. (1) a step of partially fluorinating a perfluoropolyether compound having carboxylic acid groups at both ends; (2) modifying the terminal carboxylic acid group and silylating it to a reactive silyl group; (3) A process of converting reactive silyl groups into silazane
[0024] (1) In the step of partially fluorinating a perfluoropolyether compound having carboxylic acid groups at both ends, the perfluoropolyether compound having carboxylic acid groups at both ends may be represented by the following formula: In the following formula, each repeating unit may be bonded randomly. HOOC-CF 2 O-(CF 2 O) p'-1 (C 2 F 4 O) q' -CF 2 COOH (In the formula, p' is 3 and q' is 3.) HOOC-CF 2 O-(CF 2 O) p'-1 (C 2 F 4 O) q' -CF 2 COOH (In the formula, p' is 9 and q' is 8.) HOOC-CF 2 O-(CF 2 O) p'-1 (C 2 F 4 O) q' -CF 2 COOH (In the formula, p' is 8 and q' is 9.) HOOC-CF 2 O-(CF 2 O) p'-1 (C 2 F 4 O) q' -CF 2 COOH (In the formula, p' is 12 and q' is 13.) HOOC-CF 2 O-(CF 2 O) p'-1 (C 2 F 4 O) q' -CF 2 COOH (In the formula, p' is 13 and q' is 12.) HOOC-C 3 F 6O-(C 3 F 6 O) r'-1 -CF 2 CF 2 COOH (In the formula, r' is 6, 7 or 8.) HOOC-C 3 F 6 O-(C 3 F 6 O) r'-1 -CF 2 CF 2 CF 2 COOH (In the formula, r' is 6, 7 or 8.) HOOC-CF 2 O-(C 2 F 4 O) q' (C 4 F 8 O) s' -CF 2 COOH (In the formula, q' is 4 and s' is 3.) HOOC-CF 2 O-(C 2 F 4 O) q' (C 4 F 8 O) s' -CF 2 CF 2 CF 2 COOH (In the formula, q' is 4 and s' is 3.)
[0025] A method for partially fluorinating a perfluoropolyether compound having carboxylic acid groups at both ends can be performed by introducing fluorine gas. In this reaction, the amount of fluorine gas supplied is adjusted to control the fluorination, thereby forming a terminal -CF 3 The introduction rate of the group can be appropriately adjusted. 3The introduction rate of the group is 50 mol% or more, more preferably 60 mol% or more, even more preferably 70 mol% or more, and particularly preferably 70 to 80 mol%, based on the total COOH groups. If the introduction rate is above this level, the resulting product is a mixture of a perfluoropolyether compound having a carboxylic acid group at one end and a perfluoropolyether (nonfunctional polymer) that does not have a carboxylic acid group at its end.
[0026] These mixtures can be separated by adsorption treatment, rectification, or molecular distillation. For example, the adsorption treatment can be a method using an acid adsorbent such as an anion exchange resin. In this method, first, a polymer having a carboxylic acid at its end is adsorbed to an acid adsorbent dispersed in a fluorine-based solvent. This process can remove the non-functional polymer. Thereafter, the resin is washed away with a fluorine-based solvent and a strong acid. In this process, the strong acid is adsorbed to the anion exchange resin, and the polymer having a carboxylic acid at its end is eluted into the fluorine-based solvent. In this process, the polymer containing a carboxylic acid group at one end is eluted, so that a mixture containing the polymer containing a carboxylic acid group at one end at high purity can be obtained.
[0027] In rectification or molecular distillation, the molecular terminals with fewer functional groups evaporate under milder conditions, so that a mixture containing a high purity of a polymer containing a carboxylic acid group at one end can be obtained by first separating the non-functional polymer and then separating the polymer containing a carboxylic acid group at one end. Examples of molecular distillation apparatuses used for molecular distillation include a pot molecular distillation apparatus, a falling film molecular distillation apparatus, a centrifugal molecular distillation apparatus, and an experimental centrifugal molecular distillation apparatus. The treatment conditions can be appropriately selected, but it is preferable to use a pressure of 10 -5 Pa~10 -1 The temperature is 100 to 400°C. Adsorption removal and molecular distillation may be performed in combination. The mixing ratio of the polymer containing a carboxylic acid group at one end and the non-functional polymer is 19 -CF measured by F-NMR 3 Group and -CF 2 It can be determined by the molar ratio with the COOH group.
[0028] In the step (2), the terminal carboxylic acid groups of the partially fluorinated perfluoropolyether compound obtained above are modified by first converting the terminal carboxylic acid (-COOH) of the compound to a hydroxyl group, then to an iodine group, and then introducing a divalent hydrocarbon group having 2 to 11 carbon atoms and containing a terminal aliphatic unsaturated group.
[0029] The introduction method may be according to a known method. For example, the fluorooxyalkylene group-containing polymer containing a linking group consisting of the unsubstituted divalent hydrocarbon group can be produced by first subjecting a mixture of polymers containing a carboxylic acid group at one end to reduction using a metal hydride or catalytic hydrogenation using a noble metal catalyst to produce a mixture of polymers containing a hydroxyl group at one end. Next, an iodine atom is introduced into the end of the polymer containing a hydroxyl group at one end to produce a fluorooxymethylene group-containing terminal iodide polymer represented by the following formula. The introduction of the iodine atom can be carried out using a known method. [ka] (In the formula, p, q, r, s, and x are the same as above. Each repeating unit may be bonded randomly.)
[0030] Next, it is preferable to react the fluorooxymethylene group-containing terminal iodide polymer represented by the above formula with a trialkyltin compound having a terminal unsaturated aliphatic hydrocarbon group in the presence of a radical initiator to introduce a divalent hydrocarbon group having 2 to 11 carbon atoms and containing a terminal aliphatic unsaturated group.
[0031] As the trialkyltin compound having a terminally unsaturated aliphatic hydrocarbon group, the following can be used. For example, tributylvinyltin, allyltributyltin, allyltriphenyltin, allyltrimethyltin, allyltriethyltin, allyltripropyltin, allyltribenzyltin, tributyl3-buten-1-yltin, tributyl-4-penten-1-yltin, tributyl-5-hexen-1-yltin, tributyl-6-hepten-1-yltin, tributyl-7-octen-1-yltin, tributyl-8-nonen-1-yltin, tributyl-9-decen-1-yltin, tributyl-10-undecen-1-yltin, and the like.
[0032] The following radical initiators can be used: For example, azobisisobutyronitrile (AIBN), 1,1'-azobis(cyclohexanecarbonitrile) (ABCN, VAZO (registered trademark)), di-t-butyl peroxide, t-butyl hydroperoxide, benzoyl peroxide, methyl ethyl ketone peroxide, and the like.
[0033] A solvent can be used in the reaction. The solvent used is not particularly limited, but it is preferable to use a fluorine-based solvent because the reaction compound is a fluorine compound. Examples of the fluorine-based solvent include 1,3-bistrifluoromethylbenzene (hexafluorometaxylene), trifluoromethylbenzene, and HFE-based solvent (NOVEC7100:C) sold by 3M. 4 F 9 OCH 3 , NOVEC7200:C 4 F 9 O.C. 2 H 5 , NOVEC7300:C 2 F 5 -CF(OCH 3 )-CF(CF 3 ) 2 ), and perfluorinated solvents (PF5080, PF5070, PF5060, etc.) also sold by 3M.
[0034] The aliphatic unsaturated group is then silylated to form a reactive silyl group by reacting the terminal of the aliphatic unsaturated group with chlorosilane in a known manner, thereby introducing a silyl group to the terminal.
[0035] Finally, in step (3), the silyl group of the polymer containing a silyl group at one end is converted to a silazane to obtain the target compound. The conversion can be achieved by blowing in ammonia gas in a known manner.
[0036] [Surface treatment agent] In the present invention, a surface treatment agent can be obtained using the above-mentioned perfluoropolyether-modified polysilazane as an active ingredient. In this case, a partial hydrolysis condensate of the above-mentioned perfluoropolyether-modified polysilazane can also be used.
[0037] The surface treatment agent of the present invention may be used after diluting with a suitable solvent. Examples of such solvents include fluorine-modified aromatic hydrocarbon solvents such as m-xylene hexafluoride and benzotrifluoride, fluorine-modified ether solvents such as methyl perfluorobutyl ether, ethyl perfluorobutyl ether, and perfluoro(2-butyltetrahydrofuran), and fluorine-modified alkylamine solvents such as perfluorotributylamine and perfluorotripentylamine. In particular, m-xylene hexafluoride and ethyl perfluorobutyl ether are preferred in terms of solubility, wettability, etc. The above solvents may be used alone or in combination of two or more, and in any case, it is preferable to use a solvent that dissolves the above components uniformly.
[0038] The amount of the solvent used is not particularly limited, and the optimal concentration varies depending on the treatment method, but it is preferable that the amount of the above solid content (i.e., perfluoropolyether-modified polysilazane) in the surface treatment agent is 0.001 to 10 mass %, particularly 0.01 to 5 mass %.
[0039] [Cured film] The method for surface treating a substrate or base with the thus obtained surface treatment agent can be a method of applying the surface treatment agent to the substrate or base by a known method such as brushing, dipping, spraying, or vapor deposition. The coating film thus obtained can be cured at room temperature (23±10°C, the same applies below) to form a cured coating that adheres well to the surface of various substrates or bases. The reason that this cured coating adheres well to the surface of various substrates or bases is thought to be that the silanol groups generated when the silazane bonds are hydrolyzed are highly active, which significantly increases adhesion.
[0040] The coating film applied to various substrates or base materials cures at room temperature as described above, but curing can be accelerated by heating after application by hot air treatment, infrared irradiation, or the like.
[0041] In this case, organic tin compounds (dibutyltin dimethoxide, dibutyltin dilaurate, etc.), organic titanium compounds (tetra n-butyl titanate, etc.), organic acids (acetic acid, methanesulfonic acid, etc.), and inorganic acids (hydrochloric acid, sulfuric acid, etc.) known as silanol condensation catalysts can be added. In particular, if acetic acid, tetra n-butyl titanate, dibutyltin dilaurate, etc. are added to the surface treatment agent, the curing can be further promoted. The amount of the condensation catalyst added is a catalytic amount, and is preferably 0.001 to 5 parts by mass, and particularly preferably 0.01 to 1 part by mass, per 100 parts by mass of perfluoropolyether-modified polysilazane.
[0042] The substrate to be treated with the surface treatment agent is not particularly limited, and various materials such as paper, cloth, metal and its oxides, glass, plastic, porcelain, ceramics, etc. can be used as the substrate. Specific examples include the following: As a water and oil repellent... Paper, cloth, metal, glass, plastic, ceramics, etc. As a release agent...for adhesive tapes, resin molding dies, rolls, etc. As a stain-resistant processing agent: paper, cloth, metal, glass, plastic, ceramics, etc. Others: Paint additives, resin modifiers, to modify the fluidity and dispersibility of inorganic fillers, to improve the lubricity of tapes and films, etc.
[0043] The thickness of the cured coating formed on the surface of the above-mentioned various substrates or articles is appropriately selected depending on the type of substrate.
[0044] [Goods] The surface treatment agent of the present invention can be used as a surface treatment agent for various articles, for example. That is, the present invention provides an article comprising a substrate (i.e., a substrate constituting an article) and a cured coating film of the perfluoropolyether-modified polysilazane formed on the surface of the substrate.
[0045] Specifically, a hardened coating can be formed on the surface of the following articles for the respective purposes. Examples of such coatings include touch panels and anti-reflective coatings covering the touch panel surface of smartphones, tablet PCs, smart TVs, portable media players, display advertisements, etc., cover glass for displays, tempered glass, hard coat films, anti-fingerprint coatings for resin substrates, window glass for transport vehicles such as cars, airplanes, and trains, anti-fingerprint and water- and oil-repellent coatings for interiors, anti-contamination and light-release coatings for optical members such as quartz, water- and dirt-repellent coatings for sanitary products such as bathtubs and washstands, anti-contamination coatings for general industrial glass and glass tableware, water- and dirt-repellent coatings for building materials such as building materials for exterior walls, coatings for preventing oil stains for building materials such as building materials for kitchens, anti-contamination coatings for glass for transport vehicles such as cars, trains, and aircraft (e.g., window glass, headlamp covers, etc.), water- and oil-repellent, weather-resistant, dirt-resistant, and anti-posting coatings for telephone booths, coatings for imparting water- and oil-repellent properties and anti-fingerprint adhesion properties to artworks, etc., and the like. Among these, it is preferable to use the glass for touch panels, anti-reflection films, cover glass for displays, tempered glass, glass for transport aircraft, hard coat films, cover films for displays, quartz, optical members, sanitary products, glass tableware, and building materials. EXAMPLES
[0046] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.
[0047] [Example 1] A mixture consisting of compounds represented by the following formulae (11a) and (11b) (45 mol % of (11a) and 55 mol % of (11b)) was used in the following examples. This mixture was produced by partially fluorinating a perfluorooxy compound having carboxylic acid groups at both ends with fluorine gas, and as the fluorination proceeds, the ends of the perfluorooxy compound having carboxylic acid groups at both ends are converted to fluorine groups. The content ratio (mol %) of each polymer was determined by separating the polymer having carboxylic acid by adsorbing it onto an acid adsorbent, 19 This was determined by F-NMR.
[0048] [ka] (p'=9, q'=8, q' / p'=0.89, p'+q'≒17)
[0049] (i) In a reaction vessel, 400 g of a mixture consisting of 45 mol % of the above formula (11a) and 55 mol % of the formula (11b) was dissolved in 4.0 kg of a fluorine-based solvent (PF5060 manufactured by 3M). Next, 3.2 kg of anion exchange resin B20-HG (manufactured by Organo Corporation) was added, and the mixture was stirred at 20°C for 3 hours to adsorb the compound of formula (11a) onto the anion exchange resin. After that, the anion exchange resin was washed with PF5060, and then 6 kg of PF5060 and the resin were mixed, an appropriate amount of hydrochloric acid was added, and the mixture was stirred at 20°C for 3 hours. After stirring, the mixture was left to stand for 30 minutes, and then separated into two layers, the lower layer being a fluorine layer, and the upper layer being a mixed layer of hydrochloric acid and the resin. The fluorine layer was taken out, and the PF5060 was distilled off to obtain 130 g of a product. The obtained product was 19 Measurement by F-NMR revealed that the compound was a mixture consisting of 95 mol % of the compound (11a) and 5 mol % of the compound (11b).
[0050] (ii) 50 g of the mixture obtained in the above reaction was dissolved in a mixed solvent of 100 g of m-xylene hexafluoride and 20 g of tetrahydrofuran, and 100 g of a 40% by mass solution of sodium bis(2-methoxyethoxy)aluminum hydride in toluene was added dropwise. After stirring at room temperature for 3 hours, an appropriate amount of hydrochloric acid was added, thoroughly stirred, and washed with water. Furthermore, the lower layer was taken out and the solvent was distilled off, yielding 45 g of a liquid product. 19 F-NMR and 1 It was confirmed by 1 H-NMR that the obtained product was a mixture consisting of 95 mol % of the following formula (12a) and 5 mol % of the following formula (12b).
[0051] [ka] (p'=9, q'=8, q' / p'=0.89, p'+q'≒17)
[0052] (iii) 40 g of the mixture obtained in the above step (ii), 3.4 g of iodine, 7.1 g of triphenylphosphine, and 1.8 g of imidazole were placed in a reaction vessel and stirred at 80° C. for 20 hours. Then, a saturated aqueous solution of sodium thiosulfate and an appropriate amount of acetone were added for washing. Furthermore, the lower layer was taken out, and the solvent was distilled off, yielding 39 g of a liquid product. 19 F-NMR and 1 It was confirmed by 1 H-NMR that the obtained product was a mixture consisting of 95 mol % of the following formula (13a) and 5 mol % of the following formula (13b). [ka] (p'=9, q'=8, q' / p'=0.89, p'+q'≒17)
[0053] (iv) In a reaction vessel, 20 g of the mixture obtained in the above step (iii), 1.2 g of allyltributyltin, and 20 g of hexafluorometaxylene were mixed and nitrogen was passed through. Then, 0.050 g of AIBN (azoisobutyronitrile) was added and stirred at 90°C for 16 hours. After that, the reaction product was cooled to room temperature, and the lower layer was separated by a separation operation. The obtained lower layer was washed with 20 g of hexane, and then washed with 20 g of acetone. The solvent was distilled off under reduced pressure to obtain 17.5 g of a terminally unsaturated aliphatic hydrocarbon group-modified fluorooxyalkylene group-containing polymer having a 3-butenyl group at one end represented by the following formula (14a) (a mixture of the compound of formula (14a) and the compound of formula (14b)). [ka] (p'=9, q'=8, q' / p'=0.89, p'+q'≒17)
[0054] (v) In a reaction vessel, 35 g of the mixture obtained by repeating step (iv) above several times, 4 g of trichlorosilane, and 0.1 g of a toluene solution of chloroplatinic acid / vinylsiloxane complex (2.5 × 10 -8 The mixture was aged at 110° C. for 12 hours, and the unreacted material was distilled off under reduced pressure to obtain 31 g of a liquid silyl product.
[0055] (vi) 30 g of the silyl product obtained in the above step (v) was placed in a reaction vessel and dissolved in 30 g of m-xylene hexafluoride. When dry ammonia gas was introduced, the liquid temperature rose with the introduction of ammonia gas, and ammonium chloride was generated, resulting in a cloudy state. After the ammonia gas was introduced until the mixture reached a reflux state, the introduction of ammonia gas was stopped, and stirring was continued for 2 hours under reflux. Next, the mixture was heated and stirred for 3 hours while introducing nitrogen gas, the excess ammonia gas was distilled off, the precipitated ammonium chloride was filtered off, and m-xylene hexafluoride was distilled off from the filtrate under reduced pressure to obtain 30 g of a colorless, transparent liquid. 19 F-NMR and 1 It was confirmed by 1 H-NMR that the obtained liquid was a mixture (composition 1) consisting of 95 mol % of the following formula (15a) and 5 mol % of the formula (15b). [ka] (p'=9, q'=8, q' / p'=0.89, p'+q'≒17)
[0056] [Example 2] A mixture of compounds represented by the following formulae (21a) and (21b) (45 mol % of (21a) and 55 mol % of (21b)) was used.
[0057] [ka] (p'=13, q'=12, q' / p'=0.92, p'+q'≒25)
[0058] (i) In a reaction vessel, 400 g of a mixture consisting of 45 mol % of the above formula (21a) and 55 mol % of the formula (21b) was dissolved in 4.0 kg of a fluorine-based solvent (PF5060 manufactured by 3M). Next, 3.2 kg of anion exchange resin B20-HG (manufactured by Organo Corporation) was added, and the mixture was stirred at 20°C for 3 hours to adsorb the compound of formula (21a) onto the anion exchange resin. After that, the anion exchange resin was washed with PF5060, and then 6 kg of PF5060 and the resin were mixed, and an appropriate amount of hydrochloric acid was added, followed by stirring at 20°C for 3 hours. After stirring, the mixture was allowed to stand for 30 minutes, and separated into two layers, with the lower layer being a fluorine layer and the upper layer being a mixed layer of hydrochloric acid and the resin. The fluorine layer was removed, and the PF5060 was distilled off to obtain 128 g of a product. The obtained product was 19 Measurement by F-NMR revealed that the compound was a mixture consisting of 95 mol % of the compound (21a) and 5 mol % of the compound (21b).
[0059] (ii) 50 g of the mixture obtained in the above reaction was dissolved in a mixed solvent of 100 g of m-xylene hexafluoride and 20 g of tetrahydrofuran, and 100 g of a 40% by mass toluene solution of sodium bis(2-methoxyethoxy)aluminum hydride was added dropwise. After stirring at room temperature for 3 hours, an appropriate amount of hydrochloric acid was added, thoroughly stirred, and washed with water. Furthermore, the lower layer was taken out and the solvent was distilled off, yielding 44 g of a liquid product. 19 F-NMR and 1It was confirmed by 1 H-NMR that the obtained product was a mixture consisting of 95 mol % of the following formula (22a) and 5 mol % of the following formula (22b).
[0060] [ka] (p'=13, q'=12, q' / p'=0.92, p'+q'≒25)
[0061] (iii) 40 g of the mixture obtained in the above step (ii), 2.3 g of iodine, 4.8 g of triphenylphosphine, and 1.2 g of imidazole were placed in a reaction vessel and stirred at 80° C. for 20 hours. Then, a saturated aqueous solution of sodium thiosulfate and an appropriate amount of acetone were added for washing. Furthermore, the lower layer was taken out, and the solvent was distilled off to obtain 39 g of a liquid product. 19 F-NMR and 1 It was confirmed by 1 H-NMR that the obtained product was a mixture consisting of 95 mol % of the following formula (23a) and 5 mol % of the following formula (23b). [ka] (p'=13, q'=12, q' / p'=0.92, p'+q'≒25)
[0062] (iv) In a reaction vessel, 20 g of the mixture obtained in the above step (iii), 0.8 g of allyltributyltin, and 20 g of hexafluorometaxylene were mixed and nitrogen was passed through. Then, 0.03 g of AIBN was added and stirred at 90°C for 16 hours. After that, the reaction product was cooled to room temperature, and the lower layer was separated by a separation operation. The obtained lower layer was washed with 20 g of hexane, and then washed with 20 g of acetone. The solvent was distilled off under reduced pressure to obtain 18 g of a terminally unsaturated aliphatic hydrocarbon group-modified fluorooxyalkylene group-containing polymer having a 3-butenyl group at one end, represented by the following formula (24a). [ka] (p'=13, q'=12, q' / p'=0.92, p'+q'≒25)
[0063] (v) In a reaction vessel, 35 g of the mixture obtained in the above step (iv), 2.7 g of trichlorosilane, and 0.07 g of a toluene solution of chloroplatinic acid / vinylsiloxane complex (1.8 × 10 -8 The mixture was aged at 110° C. for 12 hours, and the unreacted material was distilled off under reduced pressure to obtain 30 g of a liquid silyl product.
[0064] (vi) 25 g of the silyl product obtained in the above step (v) was placed in a reaction vessel and dissolved in 25 g of m-xylene hexafluoride. When dry ammonia gas was introduced, the liquid temperature rose with the introduction of ammonia gas, and ammonium chloride was generated, resulting in a cloudy state. After the ammonia gas was introduced until the mixture reached a reflux state, the introduction of ammonia gas was stopped, and stirring was continued for 2 hours under reflux. Next, the mixture was heated and stirred for 3 hours while introducing nitrogen gas, the excess ammonia gas was distilled off, the precipitated ammonium chloride was filtered off, and m-xylene hexafluoride was distilled off from the filtrate under reduced pressure to obtain 24.7 g of a colorless, transparent liquid. 19 F-NMR and 1 It was confirmed by 1 H-NMR that the obtained liquid was a mixture (composition 2) consisting of 95 mol % of the following formula (25a) and 5 mol % of the formula (25b). [ka] (p'=13, q'=12, q' / p'=0.92, p'+q'≒25)
[0065] [Example 3] A mixture of compounds represented by the following formulae (31a) and (31b) (45 mol % of (31a) and 55 mol % of (31b)) was used.
[0066] [ka] (r'≒7)
[0067] (i) In a reaction vessel, 400 g of a mixture consisting of 45 mol % of the above formula (31a) and 55 mol % of the formula (31b) was dissolved in 4.0 kg of a fluorine-based solvent (PF5060 manufactured by 3M). Next, 3.2 kg of anion exchange resin B20-HG (manufactured by Organo Corporation) was added, and the mixture was stirred at 20°C for 3 hours to adsorb the compound of formula (31a) onto the anion exchange resin. After that, the anion exchange resin was washed with PF5060, and then 6 kg of PF5060 and the resin were mixed, and an appropriate amount of hydrochloric acid was added, followed by stirring at 20°C for 3 hours. After stirring, the mixture was allowed to stand for 30 minutes, and separated into two layers, the lower layer being a fluorine layer, and the upper layer being a mixed layer of hydrochloric acid and the resin. The fluorine layer was taken out, and the PF5060 was distilled off to obtain 129 g of a product. The obtained product was 19 Measurement by F-NMR revealed that the compound was a mixture consisting of 95 mol % of the compound (31a) and 5 mol % of the compound (31b).
[0068] (ii) 50 g of the mixture obtained in the above reaction was dissolved in a mixed solvent of 100 g of m-xylene hexafluoride and 20 g of tetrahydrofuran, and 20 g of a 40% by mass toluene solution of sodium bis(2-methoxyethoxy)aluminum hydride was added dropwise. After stirring at room temperature for 3 hours, an appropriate amount of hydrochloric acid was added, thoroughly stirred, and washed with water. Furthermore, the lower layer was taken out, and the solvent was distilled off, yielding 46 g of a liquid product. 19 F-NMR and 1 It was confirmed by 1 H-NMR that the obtained product was a mixture consisting of 95 mol % of the following formula (32a) and 5 mol % of the following formula (32b).
[0069] [ka] (r'≒7)
[0070] (iii) 40 g of the mixture obtained in the above step (ii), 4.3 g of iodine, 8.9 g of triphenylphosphine, and 2.3 g of imidazole were placed in a reaction vessel and stirred at 80° C. for 20 hours. Then, an appropriate amount of a saturated aqueous solution of sodium thiosulfate and acetone were added for washing. Furthermore, the lower layer was taken out, and the solvent was distilled off to obtain 38 g of a liquid product. 19 F-NMR and 1It was confirmed by 1 H-NMR that the obtained product was a mixture consisting of 95 mol % of the following formula (33a) and 5 mol % of the following formula (33b). [ka] (r'≒7)
[0071] (iv) In a reaction vessel, 20 g of the mixture obtained in the above step (iii), 1.5 g of allyltributyltin, and hexafluorometaxylene V were mixed and nitrogen was passed through. Then, 0.06 g of AIBN was added and stirred at 90°C for 16 hours. After that, the reaction product was cooled to room temperature, and the lower layer was separated by a separation operation. The obtained lower layer was washed with 20 g of hexane, and then washed with 20 g of acetone. The solvent was distilled off under reduced pressure to obtain 18.3 g of a terminally unsaturated aliphatic hydrocarbon group-modified fluorooxyalkylene group-containing polymer having a 3-butenyl group at one end, represented by the following formula (34a). [ka] (r'≒7)
[0072] (v) Into a reaction vessel, 35 g of the mixture obtained in the above step (iv), 5.0 g of trichlorosilane, and 0.13 g of a toluene solution of chloroplatinic acid / vinylsiloxane complex (3.13×10 -8 The mixture was aged at 110° C. for 12 hours, and the unreacted material was distilled off under reduced pressure to obtain 32.4 g of a liquid silyl product.
[0073] (vi) 30 g of the silyl product obtained in the above step (v) was placed in a reaction vessel and dissolved in 30 g of m-xylene hexafluoride. When dry ammonia gas was introduced, the liquid temperature rose with the introduction of ammonia gas, and ammonium chloride was generated, resulting in a cloudy state. After the ammonia gas was introduced until the mixture reached a reflux state, the introduction of ammonia gas was stopped, and stirring was continued under reflux for 2 hours. Next, the mixture was heated and stirred for 3 hours while introducing nitrogen gas, the excess ammonia gas was distilled off, the precipitated ammonium chloride was filtered off, and m-xylene hexafluoride was distilled off from the filtrate under reduced pressure to obtain 29 g of a colorless, transparent liquid. 19 F-NMR and 1 By 1 H-NMR, it was confirmed that the obtained liquid was a mixture (composition 3) consisting of 95 mol % of the following formula (35a) and 5 mol % of the formula (35b). [ka] (r'≒7)
[0074] [Example 4] A mixture of compounds represented by the following formulae (41a) and (41b) (45 mol % of (41a) and 55 mol % of (41b)) was used.
[0075] [ka] (t' ≒ 3)
[0076] (i) In a reaction vessel, 400 g of a mixture consisting of 45 mol % of the above formula (41a) and 55 mol % of the formula (41b) was dissolved in 4.0 kg of a fluorine-based solvent (PF5060 manufactured by 3M). Next, 3.2 kg of anion exchange resin B20-HG (manufactured by Organo Corporation) was added, and the mixture was stirred at 20°C for 3 hours to adsorb the compound of formula (41a) onto the anion exchange resin. After that, the anion exchange resin was washed with PF5060, and then 6 kg of PF5060 and the resin were mixed, and an appropriate amount of hydrochloric acid was added, followed by stirring at 20°C for 3 hours. After stirring, the mixture was allowed to stand for 30 minutes, and separated into two layers, the lower layer being a fluorine layer, and the upper layer being a mixed layer of hydrochloric acid and the resin. The fluorine layer was taken out, and the PF5060 was distilled off to obtain 133 g of a product. The obtained product was 19 Measurement by F-NMR revealed that the compound was a mixture consisting of 95 mol % of the compound (41a) and 5 mol % of the compound (41b).
[0077] (ii) 50 g of the mixture obtained in the above reaction was dissolved in a mixed solvent of 100 g of m-xylene hexafluoride and 20 g of tetrahydrofuran, and 100 g of a 40% by mass solution of sodium bis(2-methoxyethoxy)aluminum hydride in toluene was added dropwise. After stirring at room temperature for 3 hours, an appropriate amount of hydrochloric acid was added, thoroughly stirred, and washed with water. Furthermore, the lower layer was taken out and the solvent was distilled off, yielding 47 g of a liquid product. 19 F-NMR and 1 It was confirmed by 1 H-NMR that the obtained product was a mixture consisting of 95 mol % of the following formula (42a) and 5 mol % of the following formula (42b).
[0078] [ka] (t' ≒ 3)
[0079] (iii) 40 g of the mixture obtained in the above step (ii), 4.4 g of iodine, 9.0 g of triphenylphosphine, and 2.4 g of imidazole were placed in a reaction vessel and stirred at 80°C for 20 hours. Then, an appropriate amount of a saturated aqueous solution of sodium thiosulfate and acetone were added for washing. Furthermore, the lower layer was taken out, and the solvent was distilled off to obtain 37 g of a liquid product. 19 F-NMR and 1It was confirmed by 1 H-NMR that the obtained product was a mixture consisting of 95 mol % of the following formula (43a) and 5 mol % of the following formula (43b). [ka] (t' ≒ 3)
[0080] (iv) In a reaction vessel, 20 g of the mixture obtained in step (iii) and CH 2 =CH(CH 2 ) 3 1.7 g of a tributyltin compound having - and 20 g of hexafluorometaxylene were mixed and nitrogen was passed through the mixture. Then, 0.07 g of AIBN was added and the mixture was stirred at 90°C for 16 hours. After that, the reaction product was cooled to room temperature and the lower layer was separated by a separation operation. The obtained lower layer was washed with 20 g of hexane and then with 20 g of acetone. The solvent was distilled off under reduced pressure to obtain 18.5 g of a terminally unsaturated aliphatic hydrocarbon group-modified fluorooxyalkylene group-containing polymer having a 5-hexenyl group at one end, represented by the following formula (44a). [ka] (t' ≒ 3)
[0081] (v) Into a reaction vessel, 35 g of the mixture obtained in the above step (iv), 5.0 g of trichlorosilane, and 0.13 g of a toluene solution of chloroplatinic acid / vinylsiloxane complex (3.13×10 -8 The mixture was aged at 110° C. for 12 hours, and the unreacted material was distilled off under reduced pressure to obtain 33.9 g of a liquid silyl product.
[0082] (vi) 30 g of the silyl product obtained in the above step (v) was placed in a reaction vessel and dissolved in 30 g of m-xylene hexafluoride. When dry ammonia gas was introduced, the liquid temperature rose with the introduction of ammonia gas, and ammonium chloride was generated, resulting in a cloudy state. After the ammonia gas was introduced until the mixture reached a reflux state, the introduction of ammonia gas was stopped, and stirring was continued for 2 hours under reflux. Next, the mixture was heated and stirred for 3 hours while introducing nitrogen gas, the excess ammonia gas was distilled off, the precipitated ammonium chloride was filtered off, and m-xylene hexafluoride was distilled off from the filtrate under reduced pressure to obtain 27.8 g of a colorless, transparent liquid. 19 F-NMR and 1 By 1 H-NMR, it was confirmed that the obtained liquid was a mixture (composition 4) consisting of 95 mol % of the following formula (45a) and 5 mol % of the formula (45b). [ka] (t' ≒ 3)
[0083] Preparation of surface treatment agent and formation of hardened coating The above compositions 1 to 4 were dissolved in Novec 7200 (3M, ethyl perfluorobutyl ether) to a concentration of 0.1% by mass to prepare a treatment bath. Chemically strengthened glass (50 mm x 100 mm, Corning, Gorilla) was immersed in the treatment bath for 30 seconds, then pulled out at a speed of 150 mm / min and cured at room temperature for 1 hour to form a cured coating with a thickness of about 5 nm.
[0084] [Comparative Example 1] Composition 5 shown below was prepared in place of compositions 1 to 4 above, and a cured coating was formed in the same manner as in Examples 1 to 4 using this composition. In Example 1, the mixture was prepared in the same manner as in Example 1 up to the above steps (i) and (ii), and thereafter, the mixture was prepared as follows. (iii) 40 g of the mixture obtained in the above step (ii), 15 g of allyl bromide, and 0.5 g of tetrabutylammonium hydrogen sulfate were placed in a reaction vessel and stirred at 50° C. for 3 hours, after which 10.5 g of 30% aqueous sodium hydroxide solution was added dropwise to the mixture obtained and aged at 55° C. for 12 hours. Then, an appropriate amount of PF5060 and hydrochloric acid were added and stirred, followed by thorough washing with water. Furthermore, the lower layer was removed and the solvent was distilled off, yielding 35 g of a liquid product. 19 F-NMR and 1 It was confirmed by 1 H-NMR that the obtained product was a mixture consisting of 95 mol % of the following formula (53a) and 5 mol % of the following formula (53b). [ka] (p'=9, q'=8, q' / p'=0.89, p'+q'≒17)
[0085] (iv) Into a reaction vessel, 35 g of the mixture obtained in the above step (iii), 4 g of trichlorosilane, and 0.1 g of a toluene solution of chloroplatinic acid / vinylsiloxane complex (2.5 × 10 -8 The mixture was aged at 110° C. for 12 hours, and the unreacted material was distilled off under reduced pressure to obtain 31 g of a liquid silyl product.
[0086] (v) 30 g of the silyl product obtained in the above step (iv) was placed in a reaction vessel and dissolved in 30 g of m-xylene hexafluoride. When dry ammonia gas was introduced, the liquid temperature rose with the introduction of ammonia gas, and ammonium chloride was generated, resulting in a cloudy state. After the ammonia gas was introduced until the mixture reached a reflux state, the introduction of ammonia gas was stopped, and stirring was continued under reflux for 2 hours. Next, the mixture was heated and stirred for 3 hours while introducing nitrogen gas, the excess ammonia gas was distilled off, the precipitated ammonium chloride was filtered off, and m-xylene hexafluoride was distilled off from the filtrate under reduced pressure to obtain 30 g of a colorless, transparent liquid. 19 F-NMR and 1 By 1 H-NMR, it was confirmed that the obtained liquid was a mixture consisting of 95 mol % of the following formula (54a) and 5 mol % of the formula (54b) [composition 5]. [ka] (p'=9, q'=8, q' / p'=0.89, p'+q'≒17)
[0087] The resulting cured coating was evaluated by the following methods, and the results are shown in Table 1.
[0088] [Evaluation of water and oil repellency] The glass having the cured coating formed thereon as prepared above was used to measure the contact angle of the cured coating to water (water repellency) and the contact angle of the cured coating to oleic acid (oil repellency) using a contact angle meter DropMaster (manufactured by Kyowa Interface Science Co., Ltd.).
[0089] [Evaluation of fingerprint wipe-off] A fingerprint was left on the glass surface on which the cured coating prepared above was formed, and the surface was wiped with Bemcot (manufactured by Asahi Kasei Corporation). The ease of wiping off the fingerprint was evaluated by seven panelists and classified according to the following criteria. A: It can be wiped off completely within 3 times. B: Can be wiped off completely within 10 times. C: Cannot be wiped off.
[0090] [Evaluation of slipperiness] The glass surface on which the cured coating film produced above was formed was rubbed with Bemcot (manufactured by Asahi Kasei Corporation), and the slipperiness was evaluated by seven panelists and classified according to the following criteria. A: The feel is particularly good. B: It feels good. C: It feels bad.
[0091] [Evaluation of wear resistance] The glass surface on which the cured coating film prepared above was formed was rubbed using a rubbing tester under the following conditions, and then the water contact angle was measured in the same manner as above. Evaluation environment conditions: 25°C, humidity 40% Rubbing material: The tip of the tester that comes into contact with the sample (10 mm x 10 mm) was wrapped in eight layers of Bemcot (manufactured by Asahi Kasei Corporation) and secured in place with a rubber band. Load: 500g Distance of friction (one way): 40mm Scraping speed: 1,800mm / min Number of trips: 5,000
[0092] [Table 1]
[0093] Next, the cured coatings obtained in Example 1 and Comparative Example 1 were evaluated by the following methods. The results are shown in Table 2.
[0094] [UV resistance evaluation (UV test)] The glass on which the hardened coating film produced in Example 1 and Comparative Example 1 was formed was irradiated with a metal halide lamp at an irradiance of 770 W / m 2 The specimen was irradiated with UV light (wavelength range 300 to 400 nm) for 180 hours, after which the contact angle of the surface with respect to water (water repellency) was measured in the same manner as above. In addition, the percentage decrease in water repellency was calculated as (water repellency (contact angle) of the cured film before UV light irradiation - water repellency (contact angle) of the cured film after UV light irradiation) / (water repellency (contact angle) of the cured film before UV light irradiation) x 100 (%).
[0095] [Table 2]
[0096] Comparative Example 1, which has an ether bond in the linking group, has the same water repellency as Example 1 before UV light irradiation, but after UV light irradiation, the contact angle was lower than in Example 1, indicating that the UV resistance was inferior. [Industrial Applicability]
[0097] The perfluoropolyether-modified polysilazane of the present invention has a silazane reactive group, and therefore is SiO 2Even without the use of a primer such as , it has high reactivity with the substrate and can be cured at room temperature. In addition, compared to conventional silazane compounds, it has excellent UV resistance, and has the same level of slipperiness, fingerprint wiping ability, slippery feel, and abrasion resistance. Therefore, it is useful as a water- and oil-repellent layer for optical products such as touch panel displays and anti-reflective films, sanitary products, sanitary ware, etc.
Claims
1. A perfluoropolyether-modified polysilazane consisting only of silazane units represented by the following formula (1): 【Chemistry 1】 (In the formula, Q is an alkylene group having 3 to 12 carbon atoms, p, q, r, and s are integers of 0 or more, p+q+r+s is an integer of 4 to 200, and each repeating unit may be bonded randomly. x is an integer of 1 to 3.)
2. In the above formula (1), 【Chemistry 2】 The perfluoropolyether portion represented by the following formula: 【Chemistry 3】 (In the formula, p, q, r, and s are the same as above, and each repeating unit may be bonded randomly.) The perfluoropolyether-modified polysilazane according to claim 1, which is represented by any one of the following formulas:
3. 3. The perfluoropolyether-modified polysilazane according to claim 1, wherein in the formula (1), Q is an alkylene group having 3 or 4 carbon atoms.
4. Wavelength 300-400nm, irradiance 770W / m 2 The perfluoropolyether-modified polysilazane according to any one of claims 1 to 3, which gives a cured product having a water repellency reduction rate of 15% or less after 180 hours of irradiation with UV light compared to before irradiation with UV light.
5. A surface treatment agent comprising the perfluoropolyether-modified polysilazane according to any one of claims 1 to 4.
6. A cured coating of the perfluoropolyether-modified polysilazane according to any one of claims 1 to 4.
7. 7. An article comprising a substrate and a cured coating of the perfluoropolyether-modified polysilazane according to claim 6 formed on the surface of the substrate.
8. 8. The article according to claim 7, wherein the substrate is a touch panel, an anti-reflection film, a cover glass for a display, a tempered glass, a glass for a transport machine, a hard coat film, a cover film for a display, quartz, an optical member, a sanitary product, a glass tableware or a building material.
Citation Information
Patent Citations
Perfluoropolyether-modified polysilazane and surface treatment agent using the same
JP2010043251A
Perfluoropolyether modified polysilazane and its manufacturing method, surface treatment agent and article treated by the same
JP2014105235A
Allyl group-modified fluorooxyalkylene group-containing polymer and method for producing the same
JP2015101624A
Perfluoro(POLY)ether group-containing silane compound
JP2018150508A
Perfluoro (POLY) ether group-containing silane compound
JP2019070100A